1975
DOI: 10.1007/bf00389880
|View full text |Cite
|
Sign up to set email alerts
|

Competition between two closely related Tetrabothrius cestodes of the fulmar (Fulmarus glacialis L.)

Abstract: The two congeneic Tetrabothrius cestodes of the fulmar are so closely related that they can only be reliably distinguished by differences in the number of testes. The two species show a considerable distributional overlap along the intestine. Statistically it can be shown that high numbers of the common, anteriorly situated species (T. minor) affect the distribution of the rarer, more posteriorly situated species (T. procerus), causing the latter to occupy a more posterior site in the intestine. Several possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…In an earlier study in Britain, Riley (1972) found that prevalence of parasitic nematodes in Fulmars was 83% with seven worms per infected bird (maximum 23). Similarly, Riley and Wynne Owen (1975) found 100% prevalence of cestodes in 30 Fulmars from Britain, with an intensity of 110 per bird (maximum 610; note that intensity of infection was greatest in July, the same time as our collections). Foster et al .…”
Section: Discussionsupporting
confidence: 65%
“…In an earlier study in Britain, Riley (1972) found that prevalence of parasitic nematodes in Fulmars was 83% with seven worms per infected bird (maximum 23). Similarly, Riley and Wynne Owen (1975) found 100% prevalence of cestodes in 30 Fulmars from Britain, with an intensity of 110 per bird (maximum 610; note that intensity of infection was greatest in July, the same time as our collections). Foster et al .…”
Section: Discussionsupporting
confidence: 65%
“…The importance of interaction between congeners is particularly obvious in our depauperate system. Furthermore, in at least three studies (Pojmanska 1982, Riley andOwen 1975, and the present analysis) the respective sizes of the congeneric populations were found to be important.…”
Section: Discussionsupporting
confidence: 55%
“…We also questioned the importance of congeners in determining the structure of a community. In studies by Heyneman (1962), Paperna (1964), Pojmanska (1982), Riley and Owen (1975), Stock (1985) and Bush and Holmes (1986a), all of which demonstrated evidence for interactive communities, it was interaction largely between congeneric species that was suggested to impose structure on the communities. The importance of interaction between congeners is particularly obvious in our depauperate system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much of the evidence from birds might appear to support the predictions for Wilson's interactive (phase 2) communities (e.g. Riley and Owen, 1975;Pojmanska, 1982;Bush and Holmes, 1986a;Stock and Holmes, 1987;Goater and Bush, 1988;Edwards and Bush, 1989), their species richness clearly places them near the evolutionary end (phase 4). In mammals, the evolutionary contemporaries of birds, we find less evidence for interactive communities, despite the fact that they exhibit similar levels of species richness.…”
Section: A Fair Test?mentioning
confidence: 88%